Perubahan Konstitusi : Dinamika Politik Dan Hukum Dalam Negara Yang Demokratis - Firmansyah, Firmansyah (Istinbath : Jurnal Hukum, 2021)
The constitution is essentially the legal basis of a country, and has a function as a tool of social control, meaning that the law determines the charac-teristics of society. However, the law must be able to respond to changing conditions of the people. This paper uses a normative legal research method, with a conceptual approach. The data source is secondary legal materials, which are analyzed qualitatively. Talking about changing the constitution, there are several aspects that need to be studied carefully. First, the relationship between the constitution and the dynamic condition of society. Second, the aspect of domination between politics and law. When correlated, the constitution and society have a dynamic relationship, meaning that the constitution can follow changes and the dynamics of development in society. As for carrying out the formation and amendment of the constitution, politics and law are two aspects that complement each other and act as a counterweight to each other. Therefore, community involvement in the formation and amendment of the constitution is some-thing that must be considered.